Relationship between performance appraisal and employee engagement among administrative staff - Rosmiza, Ahmad (2015)
The purpose of this study is to determine the relationship between performance appraisal and employee engagement among administrative staff. For this study, the researcher conducts a study in the context of Universiti Utara Malaysia (UUM), one of the public universities located in northern area in Malaysia. Besides, this study also determines the level of engagement among employees in UUM and does performance appraisal system influence employee engagement. A total 400 questionnaires were distributed to the administrative staff in UUM; Three hundred and six (306) usable questionnaires were returned. The data were analysed using Pearson Correlation analysis. The result indicated that the performance appraisal has significant relationship with employee engagement. On the other hand, the result shows the level of engagement among employees in UUM is high. This study shows the positive relationship between these two variables; whereas; when employee’s perception of performance appraisal (pertaining to tool; appraiser; growth and development) is high, the employee engagement among employee also high. This study also shows it is important for organization to ensure that performance appraisal conducted efficiently since it is one of the important areas in human resource management; which also may contribute towards high employee engagement among staff in organization.